Fatores associados à não realização de exame preventivo de câncer do colo do útero - Sabrina Daros Tiensoli (2015)
Cervical cancer is a major public health burden worldwide, a leading cause of death among women and the third most common type of cancer among Brazilian women. A strategic action to reduce morbimortality rates related to this cancer is the early detection, and Pap smear test is the recommended method for cervical cancer screening in Brazil with a targeted population of women aged 25-64 years old. Objective: To identify factors associated with non-screening of cervical cancer. Methods: This is a cross-sectional study which used data from the Surveillance System for Risk and Protective Factors for Chronic Diseases by Telephone Survey (Vigitel) in 2013. All women were studied in the target age range of screening, totaling 22.580 women. We evaluated the prevalence of not having regular screening according to sociodemographic characteristics (region, marital status, schooling), behavioral (physical activity during leisure time, recommended intake of fruits and vegetables, smoking and alcohol abuse, negative health behavior score) and health indicators (body max index, self-rating of health status and having health insurance). All of the analyses were processed in the Survey module of the Statistical Software (Stata), version 12.1. Results: We found 17.1% of Brazilian women had not been screened once in the last three years. The factors associated with non-screening were: women residing in the Northeast region (OR=2,01; 95%CI: 1,61-2,50), Mid-west (OR=1,84; 95%CI: 1,44-2,36) and North (OR=1,49; 95%CI: 1,16-1,90), who reported not having a partner (OR=2,21; 95%CI: 1,91-2,55), who studied between 0-8 years (OR=1,56; 95%CI: 1,27-1,91) and 9-11 years (OR=1,32; 95%CI: 1,09-1,58), with malnutrition (OR=1,62; 95%CI: 1,11-2,36), who self-rated her health status as negative (OR=1,35; 95%CI: 1,15-1,57) and who had at least one negative health behavior (OR=1,57; 95%CI: 1,25-1,95). Conclusions: Our results indicate higher rates of unscreened women by Pap smear test in population subgroups. These findings may help the planning of public policies to control cervical cancer, which ought to consider the uneven coverage and more vulnerable groups. These findings also reinforce the need for interventions aimed at promoting equity and integrated care in health services.